Absence of cardiac siderosis by MRI T2* despite transfusion burden, hepatic and serum iron overload in Lebanese patients with sickle cell disease - Inati, Adlette (2009)
Background:  The use of magnetic resonance imaging (MRI) to detect organ-specific iron overload is becoming increasingly common. Although hepatic iron overload has been recognized in patients with sickle cell disease (SCD), cardiac iron deposition has only been examined in a few reports. Methods:  This was a cross-sectional study of 23 patients with SCD. Patient charts were reviewed and data collected for drug use, total lifetime transfusions (TLT), transfusion rate (TR), status of the spleen, and comorbid illnesses or infections. Blood samples were obtained for assessment of hemoglobin, serum ferritin, non-transferrin-bound iron (NTBI), and liver enzyme levels. Doppler echocardiography was performed to detect pulmonary hypertension (PHT) and assess left ventricular ejection fraction. Cardiac iron levels were measured by MRI T2*. Direct determination of liver iron concentration (LIC) was performed using R2 MRI. In this study, cardiac T2* >20 ms was considered normal. Results:  The mean age was 24.4 ± 9.7 yr, with a male to female ratio of 15:8. A total of 9 (49.9%) patients were splenectomized. The mean TR was 14.1 ± 13.2 Units/yr, and the mean hemoglobin level was 9.0 g/dL. PHT was detected in 6 (27.3%) patients, but none had evidence of heart failure. The mean serum ferritin, LIC, and NTBI levels were 997.7 ng/mL, 4.6 mg Fe/g dw, and 1.1 ± 2.2, respectively. TR was a much better predictor of iron burden (LIC, ferritin, NTBI) than TLT. In fact, TR less than 10 Units/yr did not produce significant iron overload reflecting spontaneous losses as high as 0.11 mg/kg/d. None of the patients had evidence of cardiac iron overload (mean cardiac T2* = 37.3 ± 6.2 ms; range: 21.9–46.8 ms). There was also no statistically significant correlation between cardiac T2* values and any of the study variables. Conclusion:  Our study demonstrates that TR is a stronger predictor of iron overload than TLT. It also confirms cardiac sparing in patients with SCD, even in subjects with significant transfusion burden, systemic and hepatic iron overload.